Herpes zoster with complications in elderly patients (Research, Society and Development, 2021)
Herpes Zoster (HZ) is an acute infection caused by the varicella-zoster virus, when it reactivates latent in nerve cells of individuals who have had chickenpox. The mechanism of viral reactivation is still unknown, but it is believed to be related to some type of immunity deficiency. The disease most commonly affects immunosuppressed and elderly individuals. Clinically, it is characterized by vesiculobullous lesions distributed in the region innervated by the affected nerve, causing severe pain. This article reports two cases in elderly patients who complained of oral and cutaneous lesions with painful symptoms. In both cases the lesions involved the trigeminal nerve, with hearing impairment. The cases evolved with complications such as Postherpetic Neuralgia and Ramsay Hunt Syndrome. Antiviral, analgesic, antibiotic and laser therapy were prescribed. In none of the cases there was a recurrence within the 3-year follow-up period. Dental surgeons need to be aware of vesicular lesions - bullous that affect the skin and mucous membranes unilaterally, accompanied by symptoms of itching and pain, especially in the elderly, as they are at increased risk of developing HZ with complications and need for hospitalization.